EFEKTIVITAS PEMANFAATAN E-LEARNING DAN PLATFORM DIGITAL TERHADAP INTERAKSI GURU-SISWA DI PESANTREN - Ahmad Khori; Dedi Sukandar; Halimatus Shofiyyah (STKIP Subang, 2026)
The digital transformation has significantly altered learning patterns in Indonesian Islamic boarding schools (pesantren). Based on official data from the Ministry of Religious Affairs, there were 39,043 registered pesantren with 4.08 million students (santri) in 2022/2023, making the pesantren network one of the largest non-formal education systems in Southeast Asia. Despite this scale, adoption of digital technology remains uneven. This study examines the effectiveness of e-learning and digital platforms in mediating teacher-student interaction within the pesantren context. A qualitative approach combining systematic literature review (SLR) and phenomenological analysis was applied to 20 peer-reviewed sources published between 2013 and 2024. Findings show that e-learning increases student participation, learning flexibility, and access to diverse resources. However, it has not been able to replicate the depth of emotional closeness, spiritual mentorship (uswah hasanah), and character formation that define pesantren education. Indonesia's national digital literacy index stood at 3.54 out of 5 in 2022, indicating a moderate readiness level among educators. Blended learning is proposed as the most contextually appropriate solution, combining technological advantages with the humanistic and spiritual values central to Islamic education. Three determinant factors for successful implementation are identified: teachers' digital-pedagogical competence, humanistically oriented instructional design, and institutional policies that embed pesantren values within digital learning environments.